Research and developments of software-defined radio technologies in Japan. - Nakajima, N. (IEEE Communications magazine)
Software-defined radio technologies are attractive for future mobile communication systems because of reconfigurable and multimode operation capabilities. The reconfigurable feature is useful for enhancing functions of equipment without replacing hardware. Multimode operation is essential for future wireless terminals because a number of wireless communication standards will still coexist. Research efforts on SDR have become very active in Japan, and various kinds of SDR prototypes have been developed. This article introduces the trends of Japanese wireless communication systems and the role of SDR technologies for the future wireless systems. R&D activities for the SDR in the field of academia and industry are also presented including examples of SDR prototypes